Art, education, and cultural renewal : essays in reformational philosophy - Zuidervaart, Lambert (McGill-Queen's University Press, 2017)
"What good is art? What is the point of a university education? Can philosophers contribute anything to social liberation? Such questions, both ancient and urgent, are the pulse of reformational philosophy. Inspired by the vision of the Dutch religious and political leader Abraham Kuyper, reformational philosophy pursues social transformation for the common good. In this companion volume to Religion, Truth, and Social Transformation, Lambert Zuidervaart presents a socially engaged philosophy of the arts and higher education. Interacting with the ideas of leading Kuyperian thinkers such as Calvin Seerveld and Nicholas Wolterstorff, Zuidervaart shows why renewal in the arts needs to coincide with political and economic transformation. He also calls for education and research that serve the common good. Deeply rooted in reformational philosophy, his book brings a fresh and inspiring voice to current discussions of religious aesthetics and Christian scholarship. Art, Education, and Cultural Renewal is a testament to the practical and intellectual richness of a unique religious tradition, compelling in its call for social solidarity and cultural critique."--